Presettlement schooling behaviour of a priacanthid, the Purplespotted Bigeye Priacanthus tayenus (Priacanthidae: Teleostei) - Santana-Garcon, J.; Leis, J.; Newman, Stephen; Harvey, Euan (Springer, 2014)
We report in situ behavioural observations of presettlement schooling in Priacanthus tayenus off Coral Bay, Western Australia collected using pelagic Baited Remote Underwater stereo-Video systems. Two groups of fish (8 and 9 individuals) were observed that aggregated into a single school. Mean total length was 24.1 mm (12.5–30.2 mm). The fish swam at a mean speed of 8.5 cm s−1 in a group spacing themselves more or less evenly at a distance of around one body length from the nearest neighbour within the school. P. tayenus appeared to be sometimes associated with juveniles of other species. The results presented here add to the limited, but growing body of literature on the schooling behaviour of the early pelagic stages of demersal fishes.